Postactivation potentiation in distance runners after two different field running protocols - Boullosa, D. A.; Tuimil, J. L (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to compare jumping capacity after performing the Université de Montréal Track Test (UMTT) and the time limit (Tlim) at maximal aerobic speed. At the end of the competitive season, 12 well-trained male endurance runners performed the UMTT and Tlim tests on 2 different days separated by 48 hours to 7 days. Countermovement jump (CMJ) performance was assessed before and at the second and seventh minute after the 2 running protocols. An enhanced CMJ was observed at the second minute of recovery after UMTT and Tlim (p = 0.000; p = 0.015, respectively) and remained elevated only after the UMTT (p = 0.000). No significant correlations were found between jump and endurance field running performance. It is concluded that the postactivation potentiation profile after fatiguing running exercises in distance runners is protocol dependent with the mechanism yet to be determined.